The extent of mastery of reading and arithmetic skills among students of the first three grades under the Corona Pandemic from the teachers' point of view - Abu Jablah, Fahed AbdulKareem (Journal of Educational and Psychological Sciences, 2022)
The aimed of the study aimed to identify the extent of mastery of reading and arithmetic skills among students of the first three grades in light of the Corona pandemic from the teachers’ point of view. Reading and arithmetic skills, and its psychometric properties were verified before applying it, and the data were analyzed using one-way analysis of variance (ANOVA), The results of the research showed that the level of mastery of reading and arithmetic skills among students of the first three grades in light of the Corona pandemic was a medium level, and the results of the study showed that there were no statistically significant differences at the significance level (α≤0.05) between the arithmetic averages of the reading skills mastery level. And the calculation among students of the first three grades in light of the Corona pandemic from the teachers’ point of view is attributed to the variables of gender, number of years of experience and educational qualification.
Keywords: reading and arithmetic skills; Corona pandemic; teachers of the first three grades